m^2-2m-48=0

Simple and best practice solution for m^2-2m-48=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for m^2-2m-48=0 equation:

Simplifying
m2 + -2m + -48 = 0

Reorder the terms:
-48 + -2m + m2 = 0

Solving
-48 + -2m + m2 = 0

Solving for variable 'm'.

Factor a trinomial.
(-6 + -1m)(8 + -1m) = 0

Subproblem 1Set the factor '(-6 + -1m)' equal to zero and attempt to solve:

Simplifying
-6 + -1m = 0

Solving
-6 + -1m = 0

Move all terms containing m to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + -1m = 0 + 6

Combine like terms: -6 + 6 = 0
0 + -1m = 0 + 6
-1m = 0 + 6

Combine like terms: 0 + 6 = 6
-1m = 6

Divide each side by '-1'.
m = -6

Simplifying
m = -6
Subproblem 2Set the factor '(8 + -1m)' equal to zero and attempt to solve:

Simplifying
8 + -1m = 0

Solving
8 + -1m = 0

Move all terms containing m to the left, all other terms to the right.

Add '-8' to each side of the equation.
8 + -8 + -1m = 0 + -8

Combine like terms: 8 + -8 = 0
0 + -1m = 0 + -8
-1m = 0 + -8

Combine like terms: 0 + -8 = -8
-1m = -8

Divide each side by '-1'.
m = 8

Simplifying
m = 8Solutionm = {-6, 8}`